(untitled) (Human-Computer Interaction Perspectives, 2024)
BIM (Building Information Modeling) is a widely adopted industry standard for the AEC sector that enables an effective way of managing data and information throughout a project lifecycle. By integrating other technologies such as VR (Virtual Reality) and AR (Augmented Reality) with BIM, various functions of BIM can be enhanced, such as virtual walkthrough, schedule visualization, clash detection, and as-built modeling. Moreover, asset management functions during the maintenance and operation phase of facilities and infrastructure can also benefit from this kind of integration. This paper will provide a comprehensive review of several emerging technologies regarding (1) technological advancements reflected by software and hardware development, (2) applications in the design, construction and asset management through integration with BIM in all phases of projects, and (3) current state of research and practice. It will also identify some limiting factors that hinder VR/AR from further deployment, such as lack of GPS accuracy, complexity in development and unclear data security. Furthermore, this paper will present the benefits of integrating VR/AR technologies with BIM throughout the project lifecycle.